KESETARAAN STATUS DAN MASALAH MUTU LULUSAN MADRASAH - Aziz, Abdul (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
Though the status of Madrasah is equal to the other public schools, as attached in ULI Sisdiknas No 20 Tahun 2003, and some efforts have been made to improve the quality of Madrasah conceptually, problem of quality development in Madrasah and its graduates cannot be overcome adequately because it is not supported by the policy of educational budget. Changing the budget policy for Madrasah had a good momentum in compliance with political reformation, in which some Madrasah graduates came into as legislatosi; politicians, bureaucrats, and so forth. They, of course, can participated in making decision, mainly in making a national budget. Besides, the real condition faced by Madrasah in the globalization era is how can Madrasah be survive, how can it produce competitive outputs in this era without leaving out its characteristic and labels as Islamic institution. Another serious challenge is the problem of replacement of Moslem's orientation , from education as a medium of getting knowledge to preparation for getting ajob.